2011
DOI: 10.1063/1.3669389
|View full text |Cite
|
Sign up to set email alerts
|

Window layer with p doped silicon oxide for high Voc thin-film silicon n-i-p solar cells

Abstract: We investigate the influence of the oxygen content in boron-doped nanocrystalline silicon oxide films (p-nc-SiOx) and introduce this material as window layer in n-i-p solar cells. The dependence of both, optical and electrical properties on the oxygen content is consistent with a bi-phase model which describes the p-nc-SiOx material as a mixture of an oxygen-rich (O-rich) phase and a silicon-rich (Si-rich) phase. We observe that increasing the oxygen content enhances the optical gap E04 while deteriorating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 24 publications
3
33
0
Order By: Relevance
“…So the insertion of the n-SiOx results in the improvement of the intrinsic material properties, and the introduction of the p-SiO x only contributes to the interface improvement, which is consist with the recent result. 27 As we know SiO x is a mixed-phased nanomaterial consisting of nanometer silicon wire embedded in silicon oxide phase, 28 it has a strong electrical anisotropy that the transverse conductivity is expected to be larger than the lateral conductivity; the low lateral conductivity helps to quench the undesired local current drains at the interface or in the intrinsic layer, while the high transverse conductivity maintains the low series resistance. 29 The absolute increase in V oc and J sc lead to a dramatic improvement of the tandem cell efficiency.…”
mentioning
confidence: 99%
“…So the insertion of the n-SiOx results in the improvement of the intrinsic material properties, and the introduction of the p-SiO x only contributes to the interface improvement, which is consist with the recent result. 27 As we know SiO x is a mixed-phased nanomaterial consisting of nanometer silicon wire embedded in silicon oxide phase, 28 it has a strong electrical anisotropy that the transverse conductivity is expected to be larger than the lateral conductivity; the low lateral conductivity helps to quench the undesired local current drains at the interface or in the intrinsic layer, while the high transverse conductivity maintains the low series resistance. 29 The absolute increase in V oc and J sc lead to a dramatic improvement of the tandem cell efficiency.…”
mentioning
confidence: 99%
“…In the latter case, Cuony et al [9] attribute this improvement to the shunt quenching effect but it appears that it is not the dominant effect in the case of a-Si:H n-ip solar cells as reported by Biron et al [11]. Other groups reported that SiOx:H layers fabricated by glow discharge deposition from a SiH 4 -CO 2 -H 2 precursor gas mixture lead to the formation of a mixed phase (MP) material in which silicon nanocrystals are embedded into an a-SiOx:H matrix [12,13], instead of an amorphous Si-O compound corresponding to the random network model (RNM) [14,15].…”
Section: Introductionmentioning
confidence: 68%
“…In Fig. 3, the experimental V oc trend of our previous contribution is included [11]. The error in the V oc measurements shown in this contribution is ±5 mV due to the uncertainty of the substrate temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The a-Si:H top cell is approximately 270 nm thick and incorporates a recently developed highly transparent p-SiO x doped layer, contributing to high V oc . 27 The front contact is a 2.5-lm-thick boron-doped LP-CVD ZnO layer. As previously explained, EQE measurements were used to determine the J sc .…”
Section: Triple-junction Solar Cellsmentioning
confidence: 99%